Ekstraksi Titanium Dioksida (TiO2) dari Pasir Besi Pantai Tembakak Pesisir Barat sebagai Nanopartikel dengan Metode Hidrometalurgi - Lisa Rahmawati; Sudibyo; Dian Septiani Pratama; Zipora Sembiring; Suharso Suharso; Tika Anggraeni; Sarwan Sarwan (Jurusan Kimia FMIPA Universitas Lampung, 2024)
The iron sand sample came from Tembakak Beach, Pesisir Barat Regency, was prepared and then analyzed using XRF, obtained an Fe content of 58.294%; Si 18.525%; Ti 8.775%; Al 6.785%; Ca 3.885%; K 1.624%, as well as minor elements with a content below 0.5%. Titanium dioxide (TiO2) can be obtained from ilmenite (FeTiO3), by hydrometallurgical extraction methods. The extraction results were analyzed using XRF, obtained TiO2 at varying concentrations of HCl 7 Îœ of 15.033%, HCl 9 Îœ of 16.367%, and HCl 12 Îœ of 17.421%. XRD characterization of TiO2 extraction results with variations in HCl concentration of 12 Îœ shows that TiO2 has a rutile crystal phase with a tetragonal crystal structure, and has a particle size of 33.92 nm so that the TiO2 particles obtained are nanoparticles that play an important role in technological and industrial development.